Preparation method of high-performance silver alloy-based composite material

By homogenizing and mixing the silver-based microalloy powder and metal hydroxide powder in alcohol liquid and subsequent vacuum drying, thermal reduction and discharge plasma sintering treatment, the problems of high energy consumption and uneven dispersion in the preparation process of silver-based composite materials in the prior art are solved, and efficient and uniform powder dispersion and material performance are achieved.

CN119553123APending Publication Date: 2025-03-04昆明贵研新材料科技有限公司 +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411726762.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when preparing silver-based composite materials, the melt permeability method has problems such as high energy consumption and large melting point gap of raw materials, resulting in uneven dispersion. By ball milling, local overmilling and particle agglomeration are prone to occur, which affects the purity and uniformity of the product.

Method used

The silver-based microalloy powder and metal hydroxide powder were added to the alcohol liquid for homogenization and mixing. The liquid was used to disperse the powder more uniformly, and the silver-alloy-based composite material was obtained by vacuum drying and heat reduction treatment. Finally, discharge plasma sintering was performed to obtain the silver-alloy-based composite material.

Benefits of technology

It effectively improves the mixing and dispersion uniformity of powder, reduces the negative impact of the preparation method on the material, and improves the comprehensive performance of silver alloy-based composite materials. It has wide applicability and low energy consumption, which is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553123A_ABST
    Figure CN119553123A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance silver alloy-based composite material, and belongs to the technical field of silver-based composite material preparation. The preparation method comprises the following steps: (1) carrying out ball milling on pure silver powder and microalloy element powder to obtain silver-based microalloy powder; (2) silver-based microalloy powder and metal hydroxide powder are added into alcohol liquid, stirring is conducted, uniform mixing is conducted, and a mixture is obtained; (3) the mixture is subjected to vacuum drying and thermal reduction treatment, and silver alloy based composite powder is obtained; and (4) spark plasma sintering is conducted on the silver alloy-based composite powder, and the silver alloy-based composite material is obtained. The silver alloy-based composite powder is prepared by using the metal hydroxide as the raw material, so that the dispersion uniformity of a reinforcing phase in a silver matrix is effectively improved, and the comprehensive performance of the silver alloy-based composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silver-based composite material preparation, and relates to a method for preparing a high-performance silver alloy-based composite material. Background Art

[0002] Particle-reinforced silver-based composites are widely used in electrical switches, electronic packaging materials, and aerospace power systems due to their excellent electrical conductivity, thermal conductivity, mechanical properties, and arc erosion resistance. The particle reinforcement phase is evenly dispersed in the silver matrix, which can improve the mechanical properties of the composite material and enhance the arc erosion resistance without reducing the electrical conductivity and thermal conductivity of the composite material. Therefore, the uniformity of the distribution of the reinforcement phase in the silver-based material directly affects the comprehensive performance of the silver-based composite material. The more uniform the distribution of the particle reinforcement phase in the silver-based material, the more conducive it is to fully exert the reinforcement effect, so that the particle-reinforced silver-based composite material has better comprehensive performance.

[0003] At present, the reinforcing phase is usually mixed with the silver-based material by ball milling or melt infiltration to make the reinforcing phase uniformly dispersed. For example, the patent with application number 201310612538.3 discloses a preparation method of a multiphase metal oxide reinforced silver-based electrical contact material, which mixes metal silver powder with other metal element powders and performs ball milling, and introduces oxygen during the ball milling process to oxidize the metal element powder into a metal oxide reinforcing phase, and finally presses and sinters to obtain a metal oxide reinforced silver-based electrical contact material, which mixes metal silver powder with other metal element powders by ball milling and obtains metal oxide as a reinforcing phase by an internal oxidation method; another example is the patent with application number 201710626344.7 discloses a silver tin oxide The preparation process of the composite material comprises: mechanically dry-mixing tin oxide reinforcement particles and silver particles to obtain a mixed reinforcement powder for use, then pressing the mixed reinforcement powder into a prefabricated block, and finally applying pressure to allow the liquid silver solution to fully penetrate into the pores between the particles of the mixed reinforcement powder prefabricated block to obtain a silver-tin oxide composite material. The silver particles and tin oxide reinforcement particles are first mixed by mechanical dry mixing, and then the liquid silver is infiltrated into the mixed reinforcement powder prefabricated block by melt infiltration. For example, the patent with application number 202110178989.5 discloses a silver-based composite material and a preparation method thereof. During the preparation process, the skeleton, silver block or silver alloy block are mixed by high-temperature melt infiltration to prepare the silver-based composite material. However, when mixing by melt infiltration, on the one hand, the mixed raw materials need to be heated to a relatively high temperature to melt the raw materials, which consumes a lot of energy. On the other hand, the melt infiltration method needs to fully consider the melting point of the raw materials. When the melting point difference of the raw materials is large, some of the raw materials may volatilize, decompose or produce chemical reactions, affecting the uniformity of the raw material dispersion. Therefore, the applicability of the melt infiltration method is limited, and the melting points of the raw materials are required to be relatively close. At the same time, during the melt infiltration process, the temperature uniformity requirement is high. When the temperature is uneven, it is easy to cause insufficient melting, resulting in uneven mixing and dispersion of the raw materials. When mixing by ball milling, local over-grinding and particle agglomeration are prone to occur, resulting in uneven mixing and dispersion. In addition, during the ball milling process, the raw material fluidity is poor, and it usually takes a long time for ball milling to make the raw material mixing and dispersion more uniform. However, long-term ball milling is prone to excessive refinement and cold welding of the powder. At the same time, the ball milling medium may also contaminate the powder, affecting the purity and uniformity of the final product.

[0004] Therefore, it is necessary to provide a method for preparing high-performance silver alloy-based composite materials, which can further enhance the uniformity of the dispersion of the reinforcing phase in the silver-based material, reduce the impact of the mixed dispersion method on the product, reduce the restrictions on the preparation method, and improve the applicability of the preparation method. Summary of the invention

[0005] In order to overcome the problems in the background technology, the present invention adds silver-based microalloy powder and metal hydroxide powder to alcohol liquid for homogenous mixing. By utilizing the high-quality fluidity of the liquid, the powder in the liquid can be driven to move by disturbing the liquid, thereby more effectively dispersing the powder, and at the same time, the silver-based microalloy powder and the metal hydroxide powder can be mixed more evenly. After mixing, the metal hydroxide is evenly dispersed and anchored on the surface of the silver-based microalloy powder. In addition, when the powder is in the liquid, there is no mechanical friction and the like, which can effectively reduce the possibility of the raw material powder being contaminated. Even if the homogenization mixing time is long, the impact on the raw material powder is also small. In addition, the homogenization mixing process in the liquid can be carried out at a relatively low temperature (room temperature is sufficient), is not limited by the melting point of the raw materials, has a wide applicability, and has a low energy consumption.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] The preparation method comprises the following steps:

[0008] (1) ball milling pure silver powder and microalloying element powder to obtain silver-based microalloy powder, wherein the pure silver powder has a particle size of 5 to 30 μm, the microalloying element powder has a particle size of less than 1 μm, and the purity of the above powders is not less than 99.9%.

[0009] (2) adding the silver-based microalloy powder and the metal hydroxide powder obtained in the step (1) into an alcohol liquid, stirring and uniformly mixing, to obtain a mixture.

[0010] (3) The mixture obtained in step (2) is vacuum dried and thermally reduced to obtain a silver alloy-based composite powder.

[0011] (4) The silver alloy-based composite powder obtained in step (3) is subjected to spark plasma sintering to obtain a silver alloy-based composite material.

[0012] Preferably, in step (1), the microalloying element powder comprises one or two of copper, nickel, tungsten and titanium, and the added mass of the microalloying element powder is 0.1-0.5% of the mass of the pure silver powder.

[0013] Preferably, in the step (1), the ball milling speed is 300-800 r / min, the ball milling time is 12-24 h, the ball-to-material ratio is 10:1, and argon gas is used for protection during the ball milling process.

[0014] Preferably, in step (2), the metal hydroxide comprises one of magnesium hydroxide, nickel hydroxide and tin hydroxide.

[0015] Preferably, in step (2), the added mass of the metal hydroxide is 0.02-0.4% of the total mass of the silver-based microalloy powder and the metal hydroxide powder.

[0016] Preferably, in step (2), the alcohol liquid is ethanol.

[0017] Preferably, in step (2), the stirring speed is 900 to 1200 r / min, and the stirring time is 10 to 30 min.

[0018] Preferably, in step (3), the vacuum degree of vacuum drying is less than 10 -1 Pa, drying temperature is 60-80℃, and drying time is 12-24h.

[0019] Preferably, in step (3), the thermal reduction treatment is carried out in an argon-hydrogen mixed gas environment, the thermal reduction treatment temperature is 300-600° C., and the thermal reduction treatment time is 120-240 min. In the argon-hydrogen mixed gas, the hydrogen gas volume fraction is 5%, and the argon gas volume fraction is 95%.

[0020] Preferably, in step (4), the spark plasma sintering vacuum degree is less than 10 -1 Pa, the sintering temperature is 550-750℃, the holding time is 10-30min, the heating rate is 100℃ / min, and the sintering pressure is 50MPa.

[0021] Beneficial effects of the present invention:

[0022] 1. The present invention adds silver-based microalloy powder and metal hydroxide powder into alcohol liquid for homogenous mixing, fully utilizing the advantage of good liquid fluidity, effectively improving the mixing and dispersion uniformity of the powder, and reducing the negative impact of the preparation method itself on the material, so that the prepared silver alloy-based composite material has more excellent comprehensive performance.

[0023] 2. The present invention uses metal hydroxide powder as a preparation raw material. Compared with metal oxides and elemental metals, metal hydroxide itself is more brittle and is more easily dispersed by liquid during the stirring and dispersing process, thereby effectively reducing the agglomeration of the particle reinforcement phase, resulting in uneven dispersion and mixing, and affecting the performance of the silver alloy-based composite material.

[0024] 3. During the internal oxidation process, while the reinforcing phase metal is oxidized, the silver or silver alloy matrix is ​​prone to defects such as bubbles and ablation, which affect the performance of the final composite material. The process of reducing the metal hydroxide to obtain the metal oxide reinforcing phase can effectively alleviate the aforementioned defects of the silver or silver alloy matrix.

[0025] 4. The preparation method of the present invention is relatively simple, has good applicability, relatively low energy consumption, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the process flow of the preparation method of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments.

[0028] In the examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure for the experiments.

[0029] Example 1

[0030] In this embodiment, a silver alloy-based composite material is prepared by the following preparation method:

[0031] (1) Pure Ag powder with a purity of 99.9% and a particle size of 20 μm and Ni powder with a purity of 99.9% and a particle size of about 20 nm were subjected to high-energy ball milling treatment to disperse the nano-Ni powder evenly in the pure Ag powder, thereby obtaining a flaky silver-based microalloy powder, which was recorded as Ag-0.3Ni powder. During the ball milling process, the ball milling speed was 300 r / min, the ball milling time was 12 h, the ball-to-material ratio was 10:1, and the ball milling tank was filled with high-purity argon gas for protection; the amount of Ni powder added was 0.3% of the total mass of Ni powder and Ag powder, and the remainder was pure Ag matrix.

[0032] (2) Adding the Ag-0.3Ni powder and magnesium hydroxide obtained in step (1) into ethanol, stirring and homogenizing the mixture to obtain a mixed powder, wherein the stirring speed is 900 r / min and the stirring time is 30 min; the amount of magnesium hydroxide added is 0.2% of the total mass of the Ag-0.3Ni powder and the magnesium hydroxide powder, and the remainder is Ag-0.3Ni.

[0033] (3) vacuum drying and thermal reduction treatment of the mixed powder of step (2) to obtain a silver-nickel alloy-based composite material powder containing magnesium oxide; wherein the vacuum drying temperature is 60° C., the heat preservation time is 12 h, and the vacuum degree is less than 10 -1 Pa; heat treatment temperature is 400℃, holding time is 120min, and the thermal reduction treatment atmosphere is argon-hydrogen mixed gas.

[0034] (4) spark plasma sintering the composite powder treated in step (3) to obtain a silver-nickel alloy-based composite material with magnesium oxide as a reinforcing phase; during the spark plasma sintering process, the sintering temperature is 600° C., the heat preservation time is 10 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -1 Pa, heating rate 100℃ / min.

[0035] In the present embodiment, magnesium hydroxide has excellent dispersibility when stirred in ethanol, so that magnesium hydroxide is dispersed more evenly in ethanol, and thus anchored on the flaky Ag-0.3Ni powder in a relatively uniform state. During vacuum drying and thermal reduction, the anchoring position of magnesium hydroxide is basically not affected, that is, when magnesium hydroxide is reduced to obtain a magnesium oxide reinforcement phase, the position distribution of the reinforcement phase is basically the same as the position distribution of magnesium hydroxide before reduction. Therefore, the magnesium oxide reinforcement phase is also distributed on the flaky Ag-0.3Ni powder in a relatively uniform state, so that the reinforcement phase has a more excellent reinforcement effect, and ultimately the silver alloy-based composite material prepared by the present invention has excellent performance.

[0036] Example 2

[0037] In this embodiment, a silver alloy-based composite material is prepared by the following preparation method:

[0038] (1) Pure Ag powder with a purity of 99.9% and a particle size of 5 μm and W powder with a purity of 99.9% and a particle size of about 10 nm were subjected to high-energy ball milling treatment to disperse the nano-W powder evenly in the pure Ag powder, thereby obtaining a flaky silver-based microalloy powder, which was recorded as Ag-0.1W powder. During the ball milling process, the ball milling speed was 600 r / min, the ball milling time was 12 h, the ball-to-material ratio was 10:1, and the ball milling tank was filled with high-purity argon gas for protection; the amount of W powder added was 0.1% of the total mass of W powder and Ag powder, and the remainder was pure Ag matrix.

[0039] (2) Adding the Ag-0.1W powder and magnesium hydroxide obtained in step (1) into ethanol, stirring and homogenizing the mixture to obtain a mixed powder, wherein the stirring speed is 900 r / min and the stirring time is 20 min; the amount of magnesium hydroxide added is 0.1% of the total mass of the Ag-0.3Ni powder and the magnesium hydroxide powder, and the remainder is Ag-0.1W.

[0040] (3) vacuum drying and thermal reduction treatment of the mixed powder of step (2) to obtain a silver-nickel alloy-based composite material powder containing magnesium oxide; wherein the vacuum drying temperature is 70° C., the heat preservation time is 12 h, and the vacuum degree is less than 10 -1 Pa; heat treatment temperature is 400℃, holding time is 120min, and the thermal reduction treatment atmosphere is argon-hydrogen mixed gas.

[0041] (4) spark plasma sintering the composite powder treated in step (3) to obtain a silver-nickel alloy-based composite material with magnesium oxide as a reinforcing phase; during the spark plasma sintering process, the sintering temperature is 700° C., the heat preservation time is 10 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -1 Pa, heating rate 100℃ / min.

[0042] The silver alloy-based composite material prepared in this example has similar properties to the composite material in Example 1.

[0043] Example 3

[0044] In this embodiment, a silver alloy-based composite material is prepared by the following preparation method:

[0045] (1) Pure Ag powder with a purity of 99.9% and a particle size of 5 μm and Ni powder with a purity of 99.9% and a particle size of about 2 nm were subjected to high-energy ball milling treatment to disperse the nano-Ni powder evenly in the pure Ag powder, thereby obtaining a flaky silver-based microalloy powder, which was recorded as Ag-0.5Ni powder. During the ball milling process, the ball milling speed was 800 r / min, the ball milling time was 20 h, the ball-to-material ratio was 10:1, and the ball milling tank was filled with high-purity argon gas for protection; the amount of Ni powder added was 0.5% of the total mass of Ni powder and Ag powder, and the remainder was pure Ag matrix.

[0046] (2) Adding the Ag-0.5Ni powder and tin hydroxide obtained in step (1) into ethanol, stirring and homogenizing the mixture to obtain a mixed powder, wherein the stirring speed is 1200 r / min, the stirring time is 10 min, and the mixing medium is ethanol; the amount of tin hydroxide added is 0.4% of the total mass of the Ag-0.5Ni powder and the tin hydroxide powder, and the remainder is Ag-0.5Ni.

[0047] (3) vacuum drying and thermal reduction treatment of the mixed powder of step (2) to obtain a silver-nickel alloy-based composite material powder containing tin oxide; wherein the vacuum drying temperature is 80° C., the heat preservation time is 20 h, and the vacuum degree is less than 10 -1 Pa; heat treatment temperature is 300℃, holding time is 180min, and the thermal reduction treatment atmosphere is argon-hydrogen mixed gas.

[0048] (4) spark plasma sintering the composite powder treated in step (3) to obtain a silver-nickel alloy-based composite material with tin oxide as a reinforcing phase; during the spark plasma sintering process, the sintering temperature is 550° C., the heat preservation time is 20 min, the sintering pressure is 50 MPa, and the vacuum degree is <10 -1 Pa, heating rate 100℃ / min.

[0049] The silver alloy-based composite material prepared in this example has similar properties to the composite material in Example 1.

[0050] Example 4

[0051] In this embodiment, a silver alloy-based composite material is prepared by the following preparation method:

[0052] (1) Pure Ag powder with a purity of 99.9% and a particle size of 5 μm and Ni powder and W powder with a purity of 99.9% and a particle size of about 2 nm were subjected to high-energy ball milling treatment, so that nano Ni powder and W powder were dispersed and evenly distributed in pure Ag powder, and flaky silver-based microalloy powder was obtained, which was recorded as Ag-0.1Ni-0.1W powder. During the ball milling process, the ball milling speed was 500 r / min, the ball milling time was 24 h, the ball-to-material ratio was 10:1, and the ball milling tank was filled with high-purity argon gas for protection; the addition amount of Ni powder and W powder was 0.1% of the total mass of W powder, Ni powder and Ag powder, and the remainder was pure Ag matrix.

[0053] (2) Adding the Ag-0.1Ni-0.1W powder and tin hydroxide obtained in step (1) into ethanol, stirring and homogenizing, and obtaining a mixed powder, wherein the stirring speed is 1000 r / min, and the stirring time is 20 min; the amount of tin hydroxide added is 0.02% of the total mass of the Ag-0.1Ni-0.1W powder and the tin hydroxide powder, and the remainder is Ag-0.1Ni-0.1W.

[0054] (3) vacuum drying and thermal reduction treatment of the mixed powder of step (2) to obtain a silver-nickel alloy-based composite material powder containing tin oxide; wherein the vacuum drying temperature is 60° C., the heat preservation time is 24 h, and the vacuum degree is less than 10 -1 Pa; heat treatment temperature is 600℃, holding time is 240min, and the thermal reduction treatment atmosphere is argon-hydrogen mixed gas.

[0055] (4) spark plasma sintering the composite powder treated in step (3) to obtain a silver-nickel alloy-based composite material with tin oxide as a reinforcing phase; during the spark plasma sintering process, the sintering temperature is 750° C., the heat preservation time is 30 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -1 Pa, heating rate 100℃ / min.

[0056] The silver alloy-based composite material prepared in this example has similar properties to the composite material in Example 1.

Claims

1. A method for preparing a high-performance silver alloy-based composite material, characterized in that: The preparation method comprises the following steps: (1) ball milling pure silver powder and microalloy element powder to obtain silver-based microalloy powder; (2) adding the silver-based microalloy powder and the metal hydroxide powder obtained in step (1) into an alcohol liquid, stirring and uniformly mixing, to obtain a mixture; (3) vacuum drying and thermal reduction treatment of the mixture obtained in step (2) to obtain a silver alloy-based composite powder; (4) The silver alloy-based composite powder obtained in step (3) is subjected to spark plasma sintering to obtain a silver alloy-based composite material.

2. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (1), the micro-alloying element powder includes one or two of copper, nickel, tungsten and titanium, and the added mass of the micro-alloying element powder is 0.1-0.5% of the total mass of the pure silver powder and the micro-alloying element powder.

3. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (1), the ball milling speed is 300-800 r / min, the ball milling time is 12-24 h, the ball-to-material ratio is 10:1, and argon gas is used for protection during the ball milling process.

4. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (2), the metal hydroxide includes one of magnesium hydroxide, nickel hydroxide and tin hydroxide.

5. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (2), the added mass of the metal hydroxide is 0.02-0.4% of the total mass of the silver-based microalloy powder and the metal hydroxide powder.

6. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (2), the alcohol liquid is ethanol.

7. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (2), the stirring speed is 900 to 1200 r / min, and the stirring time is 10 to 30 min.

8. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (3), the vacuum degree of vacuum drying is less than 10 -1 Pa, drying temperature is 60-80℃, and drying time is 12-24h.

9. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (3), the thermal reduction treatment is carried out in an argon-hydrogen mixed gas environment, the thermal reduction treatment temperature is 300 to 600° C., and the thermal reduction treatment time is 120 to 240 minutes.

10. The method for preparing a high-performance silver alloy-based composite material according to claim 1, characterized in that: In the step (4), the spark plasma sintering vacuum degree is less than 10 -1 Pa, the sintering temperature is 550-750℃, the holding time is 10-30min, the heating rate is 100℃ / min, and the sintering pressure is 50MPa.

Citation Information

Patent Citations

  • A method for preparing a multiphase metal oxide reinforced silver-based electrical contact material

    CN103681015B

  • Preparation process of silver oxide tin composite material

    CN107523713A

  • A silver-based composite material and its preparation method

    CN112974774B